PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 124 PEKANBARU - Netty Mari Mari; Erlisnawati '; Lazim. N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research has purpose to improve the ability of student in studying IPS by applying cooperative learning method called Jigsaw in fourth grader of SD Negeri 124 Pekanbaru. Jigsaw is a cooperative method, where the student will be put in groups consist of 4 up to 5 students. To learn the materials that are devided in to several parts for each member. This research was done in February until March in 2015. The subject of this research where the 4th year students of SD 124 Pekanbaru in academic year 2014/2015, whit the number of students was 26, they are 14 boys and 12 girls. The data of this research was the data about the result of teaching and learning with Jinsaw. The technic of data collection was done by doing observation and test, and the data analysis was done with descriptive analysis. The result of data analysis can be seen from the activities of the teacher during he teaching and learning processby applying cooperative method called Jingsaw. In the first cycle, the average is 79,16% which is included to “good” category. In the second cycle, there was improvement. The average was 87,5% which is categorized to “very good”. The standard score was 52,94% whit score 63,84% which is categorized “enough”. In the first cycle, it become 57,69% whit score 69,23. In the second one, it become 80,76% with score 78,26. There fore, it concludes that applying Jigsaw cooperative method can improve the ability of the 4th year studend of SD Negeri 124 Pekanbaru in learning IPS. Keywords: Jigsaw cooperative Model, Learning Outcomes IPS.